Medical physics - Cameron, John R. (John Wiley and Sons, 1978)
Contents of this book include 20 chapers: Terminology, Modeling, and maesurement; Forces on and in the body; Physic of the Skeleton; Heat and cold in Medicine; Energy, Work and power of the body;...